Effect of Chronic Smoking on Choroidal Thickness as Measured by Swept Source OCT When Compared to Non Smokers - Shoji Kishi, Haroon Tayyab, Sana Jahangir (Pakistan Journal of Ophthalmology, 2015)
Purpose: To compare choroidal thickness between smokers and nonsmokers by utilising swept source optical coherence tomography. Material and Methods: A total of 80 subjects were included this study. Forty patients were nonsmokers and 40 patients were smokers with a minimum history of 10 years of smoking. Swept source optical coherence tomography was used to calculate central choroidal thickness as well as choroidal thickness measurements at varying distances from centre of fovea temporally and nasally. All subjects were asked to refrain from smoking at least 8 hours before measurements. Results: The choroidal thickness measurements did not vary between smokers and non smokers when measured on swept source optical coherence tomography. The duration of smoking also did not seem to influence choroidal thickness (p-value = 0.280). Conclusion: Chronic smoking does not seem to influence choroidal thickness when compared to healthy non smokers. Keywords: Swept source optical coherence tomography, choroidal thickness, smokers